Fear and Disillusionment: The EcoGothic in the Poetry of Sylvia Plath - Colin BANCROFT (E-REA)
This study will analyse elements of the EcoGothic in the poetry of Sylvia Plath, and will focus in particular on her poems set in the “Yorkshire” landscape which she visited after marrying the English poet Ted Hughes. The EcoGothic looks to evaluate environmental concerns through the Gothic lens and is a sub-strand of Ecocriticism, which in its widest definition looks to evaluate the relationships of culture on the non-human world. The EcoGothic utilises the tropes of the Gothic genre such as: monstrosity, imprisonment, fear, the Other, the Uncanny, repression, oppression and the Sublime to illuminate issues surrounding the self, relationships, landscapes and the environment. In particular this study will focus on the following areas: how Plath uses elements of the EcoGothic to explore patriarchal dominance of women: how the Yorkshire landscape represents the uncanny, developing the sense of dislocation her speakers feel from the self and their wider environment; how Plath uses elements of the American Sublime to highlight a sense of existential anxiety brought on by encounters with blank landscapes.